1995
DOI: 10.1128/jb.177.18.5199-5205.1995
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the two-enzyme system catalyzing the oxidation of the D-proline residue of pristinamycin IIB during the last step of pristinamycin IIA biosynthesis

Abstract: High levels of conversion of 14 C-labelled pristinamycin II B (PII B ) to pristinamycin II A (PII A ) were obtained in vivo in Streptomyces pristinaespiralis and in some other streptogramin A producers. This established that PII B was an intermediate on the pathway to PII A . In addition, in vitro studies with cell-free protein preparations demonstrated that the oxidation of PII B to PII A is a complex process requiring NADH, riboflavin 5-phosphate (FMN), and molecular oxygen. Two enzymes were shown to be nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 28 publications
3
108
0
Order By: Relevance
“…The K m values for NADH and different flavins (Table 1) were similar to those observed for other flavin reductases, that is, enzymes that generate free reduced flavins (10,18,21,38). It is worth noting the high K m values for FMN when compared to the K m values in the nanomolar range that have been determined for other monooxygenases, an observation that reinforces the idea that FMN acts as a substrate rather than as a prosthetic group.…”
Section: Resultssupporting
confidence: 64%
“…The K m values for NADH and different flavins (Table 1) were similar to those observed for other flavin reductases, that is, enzymes that generate free reduced flavins (10,18,21,38). It is worth noting the high K m values for FMN when compared to the K m values in the nanomolar range that have been determined for other monooxygenases, an observation that reinforces the idea that FMN acts as a substrate rather than as a prosthetic group.…”
Section: Resultssupporting
confidence: 64%
“…Liquid cultures for pristinamycin production were made as described by Thibaut et al (1995). Nosiheptide (for selection of thiostrepton resistance; Rhô nePoulenc Rorer) was used at a concentration of 400 g ml ¹1 for solid media and 2 g ml ¹1 for liquid media.…”
Section: Media and General Techniquesmentioning
confidence: 99%
“…Extraction, HPLC separation and quantification of PI and PII components PI and PII are extracted and analysed by high-performance liquid chromatography (HPLC) as previously described (Thibaut et al, 1995). Low PI concentrations were detected with a Kratos Spectroflow 980 fluorescence detector set at ᮊ 1997 Blackwell Science Ltd, Molecular Microbiology,23,[191][192][193][194][195][196][197][198][199][200][201][202] Expression of PapM in E. coli A 1.7 kb MluI-StuI fragment, harbouring the end of the papB gene and the entire papM gene, was first cloned into pMTL23, linearized by MluI and BamHI and then treated with Klenow to give pVRC706, in which the BamHI site was reconstituted.…”
Section: Media and General Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas FADH 2 most commonly serves as a redox cofactor when it is tightly bound to enzymes, free FADH 2 is used as a co-substrate for monooxygenase reactions (42)(43)(44)(45)(46), including several from E. coli strains (28,47,48). Indirect evidence has suggested that FADH 2 may also assist in the activation of ribonucleotide reductase (33).…”
Section: Nadh Is Unlikely To Be the Direct Reductant Of Free Iron-mentioning
confidence: 99%